1984
DOI: 10.1104/pp.74.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Host-Pathogen Interactions

Abstract: ABSTRACrHeat-labile elicitors of phytoalexin accumulation in soybeans (Glycine max L. Merr. cv Wayne) were detected in culture filtrates of Erwinia carotovora grown on a defed medium containing citrus pectin as the sole carbon source. The heat-labile elicitors were highly purified by cation-exchange chromatography on a CM-Sephadex (C-50) column, followed by agarose-affinity chromatography on a Bio-Gel A-05m gel filtration column. The heat-labile elicitor activity co-purified with two a- (14) and from citrus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
50
0
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 191 publications
(52 citation statements)
references
References 16 publications
1
50
0
1
Order By: Relevance
“…An apparently homogeneous preparation of the PGA lyase was shown to induce phytoalexin accumulation in soybean cotyledons and also to release uronic-acid rich, heatstable elicitors from soybean cell walls, citrus pectin, and sodium polypectate (7). Similar results have been obtained by West et al.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…An apparently homogeneous preparation of the PGA lyase was shown to induce phytoalexin accumulation in soybean cotyledons and also to release uronic-acid rich, heatstable elicitors from soybean cell walls, citrus pectin, and sodium polypectate (7). Similar results have been obtained by West et al.…”
supporting
confidence: 78%
“…Recent work has demonstrated that a heat-labile elicitor of phytoalexins produced by the phytopathogenic bacterium Erwinia carotovora var carotovora is a pectin-degrading enzyme, PGA lyase3 (7). An apparently homogeneous preparation of the PGA lyase was shown to induce phytoalexin accumulation in soybean cotyledons and also to release uronic-acid rich, heatstable elicitors from soybean cell walls, citrus pectin, and sodium polypectate (7).…”
mentioning
confidence: 99%
See 3 more Smart Citations